Anaerobic UV adhesive and preparation method thereof

The anaerobic UV adhesive formulation synchronously enhances curing depth and adhesion by integrating anaerobic and UV curing technologies, overcoming the limitations of traditional UV adhesives in deep or thick applications.

CN119144271APending Publication Date: 2024-12-17DONGGUAN APUBOND NEW MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411103592.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing UV adhesives face challenges with poor deep curing or non-curing in dark or thick layers due to limitations in light intensity and material transmittance, while anaerobic adhesives offer advantages but are not typically combined with UV curing.

Method used

An anaerobic UV adhesive formulation combining acrylic oligomer, peroxide initiator, photoinitiator, filler, and color paste, which allows for simultaneous anaerobic and UV curing, enhancing curing depth and adhesion.

Benefits of technology

The adhesive achieves deep curing and improved adhesion by combining anaerobic and UV curing mechanisms, addressing the limitations of traditional UV adhesives in dark or thick layers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144271A_ABST
    Figure CN119144271A_ABST
Patent Text Reader

Abstract

The invention discloses an anaerobic UV adhesive and a preparation method thereof, and belongs to the technical field of UV adhesives, the UV adhesive is composed of the following raw materials: an acrylic oligomer, an acrylic monomer, a peroxide initiator, a photoinitiator, a filler and a color paste.The anaerobic curing mechanism and the UV curing technology are creatively combined, and the UV adhesive is prepared from the following raw materials: the acrylic oligomer, the acrylic monomer, the peroxide initiator, the photoinitiator, the filler and the color paste.The preparation method has the advantages that the anaerobic curing mechanism and the UV curing technology are combined; after the anaerobic UV adhesive prepared by the invention is irradiated by ultraviolet light, the curing depth and the adhesive force are synchronously increased along with an anaerobic curing agent, and the anaerobic UV adhesive not only can be quickly subjected to surface drying under the irradiation of the ultraviolet light, but also can be continuously cured in a deep gap isolated from oxygen, so that the problem of insufficient curing depth of a traditional UV adhesive in deep color or thick layer application is effectively solved; and the adhesive force is correspondingly improved while the curing efficiency and the curing quality are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of UV adhesives, and more specifically to an anaerobic UV adhesive and a preparation method thereof. Background Art

[0002] The invention of UV adhesive (UV glue) can be traced back to 1955, when it was invented by American chemist James R. Cozean. In the laboratory, he discovered that special resins could be cured quickly by irradiating them with ultraviolet light, and based on this, he developed the first commercial UV glue. The main principle of UV glue is to use ultraviolet (UV) photoinitiators (or photosensitizers) to absorb ultraviolet light to produce active free radicals or cations, which in turn trigger monomer polymerization and cross-linking chemical reactions, causing the adhesive to transform from liquid to solid within seconds. It has the characteristics of fast curing, no solvent, no pollution, suitable for automated operations, a wide range of bonding materials, and high bonding strength. However, UV curing technology is limited by light intensity and the light transmittance of the material, resulting in dark-colored adhesives always facing challenges in deep curing.

[0003] To solve this problem, the existing technology either introduces a baking type heating curing step, which is effective but increases the complexity of the process and narrows the application range of the glue; or uses a fast-curing resin to increase the reaction speed and thus improve the curing depth, but inevitably increases the product cost.

[0004] Anaerobic adhesive, as a unique adhesive, has its curing reaction significantly inhibited in an oxygen environment, but once it is in a gap between bonding surfaces that is isolated from oxygen, it can quickly cure itself. Its characteristics include single-component easy operation, solvent-free and environmentally friendly, fast curing at room temperature, strong heat resistance, acid and alkali resistance, etc., so it is widely used in many fields such as bolt tightening, sealing and leak prevention, assembly and fixation, etc.

[0005] In view of this, providing an anaerobic UV adhesive that combines the advantages of anaerobic and UV curing and a preparation method thereof has become a technical problem that needs to be solved urgently in the art. Summary of the invention

[0006] In view of the defects in the prior art, the object of the present invention is to provide an anaerobic UV adhesive and a preparation method thereof, so as to solve the technical problems of poor deep curing or complete non-curing of the deep layer.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] On one hand, the present invention provides an anaerobic UV adhesive, comprising the following raw materials in parts by weight: 40-60 parts of acrylic oligomer, 40-60 parts of acrylic monomer, 1-3 parts of peroxide initiator, 1-3 parts of photoinitiator, 3-5 parts of filler, and 0.03-0.06 parts of color paste.

[0009] According to one embodiment of the present invention, the acrylic oligomer is polyurethane (meth) acrylate.

[0010] According to an embodiment of the present invention, the molecule of the polyurethane (meth) acrylate contains an acrylic functional group and a urethane bond, has a viscosity ranging from 4000 to 6000 mPa·s, and appears as a light yellow transparent liquid.

[0011] According to one embodiment of the present invention, the acrylic acid monomer is one or more of isobornyl acrylate and tetrahydrofuran acrylate.

[0012] According to one embodiment of the present invention, the peroxide initiator is a peroxide mixture.

[0013] According to one embodiment of the present invention, the photoinitiator is 1-hydroxycyclohexyl phenyl ketone.

[0014] According to one embodiment of the present invention, the filler is hydrophobic fumed silica.

[0015] According to one embodiment of the present invention, the filler type is one or more of TS720, R974 and R972.

[0016] According to one embodiment of the present invention, the color paste category is HostatintUV BLACKN30.

[0017] Another aspect of the present invention provides a method for preparing an anaerobic UV adhesive, comprising the following steps:

[0018] S1. Prepare raw materials: weigh the following raw materials by weight: 40-60 parts of acrylic oligomer, 40-60 parts of acrylic monomer, 1-3 parts of peroxide initiator, 1-3 parts of photoinitiator, 3-5 parts of filler, and 0.03-0.06 parts of color paste;

[0019] S2, mixing and stirring: adding the weighed raw materials into a stirring cup, placing the stirring cup in a blender, stirring at a rate of 1000 revolutions per minute for 100-200 seconds without turning on the vacuum pump, and stirring at a rate of 1000 revolutions per minute for 100-200 seconds with the vacuum pump turned on, to obtain a uniformly mixed glue solution;

[0020] S3. Curing and application: Apply the glue to the pre-configured substrate surface and cure it under UV light for 11 seconds. Wait until the colloid returns to room temperature to obtain a colloid with good adhesion and is difficult to peel off.

[0021] Compared with the prior art, the advantages of the present invention are:

[0022] The present invention creatively combines the anaerobic curing mechanism with the UV curing technology. After ultraviolet light irradiation, the curing depth and adhesion of the anaerobic UV adhesive prepared by the present invention increase synchronously with the anaerobic curing agent. Under ultraviolet light irradiation, it can not only quickly dry on the surface, but also continue to cure in deep gaps isolated from oxygen, effectively solving the problem of insufficient curing depth of traditional UV adhesives in dark or thick layer applications, significantly improving the curing efficiency and curing quality while also correspondingly improving the adhesion. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention; it is obvious that the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments, and all other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention; the raw materials and reagents used in the present invention are commercially available.

[0025] An anaerobic UV adhesive comprises the following raw materials in parts by weight:

[0026] 40-60 parts of acrylic oligomer, which can be one or more of polyurethane (meth) acrylate, polyester (meth) acrylate, epoxy (meth) acrylate, polyolefin (meth) acrylate and pure acrylate. The acrylic oligomer is preferably polyurethane (meth) acrylate, which contains acrylic functional groups and urethane bonds in its molecules, and is used to make the cured coating have the high wear resistance, adhesion, flexibility and high peel strength of polyurethane. Its viscosity range is 4000-6000mPa·s, and its appearance is light yellow transparent liquid. Specific products can be selected 8672, 8674 or Trust7128.

[0027] 40-60 parts of acrylic acid monomer, the acrylic acid monomer can be one or more of 4-acryloylmorpholine, isobornyl acrylate, tetrahydrofuran acrylate, cyclotrimethylolpropane formal acrylate, ethoxyphenol acrylate, tripropylene glycol diacrylate and neopentyl glycol dimethacrylate, the acrylic acid monomer is preferably isobornyl acrylate and tetrahydrofuran acrylate, the acrylic acid monomer is used to dilute the acrylic acid oligomer, cross-link with the acrylic acid oligomer, and improve the high temperature resistance, hardness and toughness of the coating.

[0028] 1-3 parts of peroxide initiator, which is a peroxide mixture, is used to provide anaerobic curing ability and improve curing depth and adhesion.

[0029] 1-3 parts of a photoinitiator, which can be one or more of 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide and 2-benzyl-2-dimethylamino-1-(4-morpholinephenyl) butanone. The photoinitiator is preferably 1-hydroxycyclohexyl phenyl ketone. The photoinitiator can absorb energy of a certain wavelength in the ultraviolet light region (250-420nm) or the visible light region (400-800nm) to generate free radicals, cations, etc., thereby initiating polymerization, cross-linking and curing of acrylic monomers and acrylic oligomers.

[0030] 3-5 parts of filler, the filler is hydrophobic fumed silica, the filler can be one or more of TS720, R974 and R972, R974 is made of a specific surface area of ​​200m 2 / g hydrophilic fumed silica is surface modified by dimethyldichlorosilane to obtain hydrophobic fumed silica; R972 is a fumed silica with a specific surface area of ​​130m 2 / g of hydrophilic fumed silica is surface-modified by dimethyldichlorosilane to obtain hydrophobic fumed silica; TS720 is a hydrophobic fumed silica obtained by surface-modifying a hydrophilic fumed silica with a medium surface area by polydimethyldichlorosilane, and the filler is preferably R972, and the filler can give the reaction system thickening and reinforcement functions, thereby improving the storage performance of the coating, and can also give the reaction system anti-caking, anti-sedimentation, anti-sagging and other functions, thereby improving the stability of the coating, and the surface of the fumed silica has a large number of silanol groups, which can directly or indirectly produce hydrogen bonds with liquid molecules to form a three-dimensional spatial network structure, thereby increasing the viscosity and thixotropy, improving the colloid stacking, and thus improving the curing depth. TS720, R974 and R972 of this embodiment are all commercially available.

[0031] The color paste is 0.03-0.06 parts. The color paste can be Hostatint UV RED D3G, Hostatint UVBLUE BG, HostatintUV BLACKN30, three color categories produced by Clariant. The color paste is preferably Hostatint UV BLACKN30, which has the characteristics of easy dispersion, high pigment content and good rheological properties.

[0032] The present invention also provides a method for preparing an anaerobic UV strippable coating, comprising the following steps:

[0033] S1. Prepare raw materials: Weigh the following raw materials by weight: 40-60 parts of acrylic oligomer, 40-60 parts of acrylic monomer, 1-3 parts of peroxide initiator, 1-3 parts of photoinitiator, 3-5 parts of filler, and 0.03-0.06 parts of color paste.

[0034] In this step, the description of each raw material has been described in detail above and will not be repeated here.

[0035] S2. Mixing and stirring: Add the weighed raw materials into a stirring cup, and place the stirring cup in a blender. Without turning on the vacuum pump, stir at a rate of 1000 revolutions per minute for 100-200 seconds. With the vacuum pump turned on, stir at a rate of 1000 revolutions per minute for 100-200 seconds to obtain a uniformly mixed glue solution.

[0036] In this step, without turning on the vacuum pump, the stirring time is preferably 120 seconds, which is used to fully mix the raw materials; when the vacuum pump is turned on, the stirring time is preferably 120 seconds, so that the colloid can be fully free of bubbles. Through this step, a uniformly mixed and bubble-free adhesive solution is obtained. After the stirring is completed, the adhesive solution can also be allowed to stand for defoaming and filtered according to actual conditions. It can be allowed to stand for a period of time to allow the bubbles to rise and burst naturally, thereby improving the transparency and uniformity of the adhesive. If there are larger particles or impurities in the adhesive solution, they can be removed by filtration, thereby improving the purity and performance stability of the adhesive.

[0037] S3. Curing and application: Apply the glue to the pre-configured substrate surface and cure it under UV light for 11 seconds. Wait until the colloid returns to room temperature to obtain a colloid with good adhesion and is difficult to peel off.

[0038] In this step, the UV irradiation energy is 3000mj / cm 2 , under laboratory conditions, the illumination time is less than or equal to 11 seconds, preferably 11 seconds.

[0039] Embodiment 1:

[0040] S1: Weigh the following raw materials by weight: 8672, 2.5g Trust7128, 2.5g isobornyl acrylate, 2.5g tetrahydrofuran acrylate, 0.3g peroxide mixture, 0.2g 1-hydroxycyclohexyl phenyl ketone, 0.4g R972, 0.005g Hostatin UVBLACKN30;

[0041] S2: Add the weighed raw materials into a stirring cup, and place the stirring cup in a blender. Stir at a rate of 1000 revolutions per minute for 120 seconds without turning on the vacuum pump. Stir at a rate of 1000 revolutions per minute for 120 seconds with the vacuum pump turned on to obtain a uniformly mixed glue solution.

[0042] S3: Apply glue to the pre-configured substrate surface and cure it under UV light for 11 seconds. Wait until the colloid returns to room temperature to obtain a colloid with good adhesion and difficult to peel off, with half of the colloid attached to the substrate surface.

[0043] Embodiment 2:

[0044] S1: Weigh the following raw materials by weight: 8672, 3g Trust7128, 2g isobornyl acrylate, 2g tetrahydrofuran acrylate, 0.2g peroxide mixture, 0.2g 1-hydroxycyclohexyl phenyl ketone, 0.4g R972, 0.005g HostatintUV BLACKN30;

[0045] S2: Add the weighed raw materials into a stirring cup, and place the stirring cup in a blender. Stir at a rate of 1000 revolutions per minute for 120 seconds without turning on the vacuum pump. Stir at a rate of 1000 revolutions per minute for 120 seconds with the vacuum pump turned on to obtain a uniformly mixed glue solution.

[0046] S3: Apply the glue to the pre-configured substrate surface and cure it under UV light for 11 seconds. Wait until the colloid returns to room temperature to obtain a colloid with good adhesion and difficult to peel off.

[0047] Embodiment 3:

[0048] S1: Weigh the following raw materials by weight: 8672, 2.5g Trust7128, 2.5g isobornyl acrylate, 2.5g tetrahydrofuran acrylate, 0.2g peroxide mixture, 0.2g 1-hydroxycyclohexyl phenyl ketone, 0.4g R972, 0.005g HostatintUV BLACKN30;

[0049] S2: Add the weighed raw materials into a stirring cup, and place the stirring cup in a blender. Stir at a rate of 1000 revolutions per minute for 120 seconds without turning on the vacuum pump. Stir at a rate of 1000 revolutions per minute for 120 seconds with the vacuum pump turned on to obtain a uniformly mixed glue solution.

[0050] S3: Apply the glue to the pre-configured substrate surface and cure it under UV light for 11 seconds. Wait until the colloid returns to room temperature to obtain a colloid with good adhesion and difficult to peel off.

[0051] Embodiment 4:

[0052] S1: Weigh the following raw materials by weight: 8672, 2g Trust7128, 3g isobornyl acrylate, 3g tetrahydrofuran acrylate, 0.2g peroxide mixture, 0.2g 1-hydroxycyclohexyl phenyl ketone, 0.4g R972, 0.005g HostatintUV BLACKN30;

[0053] S2: Add the weighed raw materials into a stirring cup, and place the stirring cup in a blender. Stir at a rate of 1000 revolutions per minute for 120 seconds without turning on the vacuum pump. Stir at a rate of 1000 revolutions per minute for 120 seconds with the vacuum pump turned on to obtain a uniformly mixed glue solution.

[0054] S3: Apply the glue to the pre-configured substrate surface and cure it under UV light for 11 seconds. Wait until the colloid returns to room temperature to obtain a colloid with good adhesion and is difficult to peel off.

[0055] Embodiment 5:

[0056] S1: Weigh the following raw materials by weight: 8672, 2.5g Trust7128, 2.5g isobornyl acrylate, 2.5g tetrahydrofuran acrylate, 0.1g peroxide mixture, 0.2g 1-hydroxycyclohexyl phenyl ketone, 0.4g R972, 0.005g HostatintUV BLACKN30;

[0057] S2: Add the weighed raw materials into a stirring cup, and place the stirring cup in a blender. Stir at a rate of 1000 revolutions per minute for 120 seconds without turning on the vacuum pump. Stir at a rate of 1000 revolutions per minute for 120 seconds with the vacuum pump turned on to obtain a uniformly mixed glue solution.

[0058] S3: Apply the glue to the pre-configured substrate surface and cure it under UV light for 11 seconds. Wait until the colloid returns to room temperature to obtain a colloid with good adhesion but not difficult to peel off.

[0059] Comparative Example:

[0060] S1: Weigh the following raw materials by weight: 8672, 2.5g Trust7128, 2.5g isobornyl acrylate, 2.5g tetrahydrofuran acrylate, 0.2g 1-hydroxycyclohexyl phenyl ketone, 0.4g R972, 0.005g HostatintUV BLACKN30;

[0061] S2: Add the weighed raw materials into a stirring cup, and place the stirring cup in a blender. Stir at a rate of 1000 revolutions per minute for 120 seconds without turning on the vacuum pump. Stir at a rate of 1000 revolutions per minute for 120 seconds with the vacuum pump turned on to obtain a uniformly mixed glue solution.

[0062] S3: The glue is applied to the pre-configured substrate surface and cured by UV light for 11 seconds. The glue is allowed to return to room temperature to obtain a glue with poor adhesion and can be easily peeled off.

[0063] The present invention performs peelability test and slicing test on the coatings prepared in Examples 1-5 and the comparative example. The test results are shown in Table 2.

[0064] Adhesion test: The test substrate is a bare PCB board, the height of the cured colloid is 5mm, and the colloid is peeled off from the PCB board manually.

[0065] Curing depth test: The test substrate is the colloid peeled from the PCB board. The colloid is cut in the middle to measure the cured thickness of the central area.

[0066] Table of raw materials and how to obtain them:

[0067]

[0068] Table 1: Weight parts of each raw material in UV adhesive

[0069]

[0070] Table 2: Results of adhesion test and curing depth test of the coatings prepared in Examples 1-5 and Comparative Examples.

[0071]

[0072] As shown in Table 2, the anaerobic UV curing adhesives prepared in Examples 1-5 increase the curing depth and adhesion of the anaerobic curing agent after UV irradiation. This effectively solves the problem of insufficient curing depth of traditional UV adhesives in dark or thick layer applications, significantly improves curing efficiency and curing quality, and also correspondingly improves adhesion.

[0073] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0074] In addition, it should be understood that although the present specification is described according to embodiments, not every embodiment contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation methods that those skilled in the art can understand.

Claims

1. An anaerobic UV adhesive, characterized in that: The invention comprises the following raw materials in parts by weight: 40-60 parts of acrylic acid oligomer; 40-60 parts of acrylic acid monomer; 1-3 parts of peroxide initiator; 1-3 parts of photoinitiator; 3-5 parts of filler; Color paste 0.03-0.06 parts.

2. The anaerobic UV adhesive according to claim 1, characterized in that: The acrylic oligomer is polyurethane (meth) acrylate.

3. The anaerobic UV adhesive according to claim 2, characterized in that: The molecule of the polyurethane (meth) acrylate contains an acrylic functional group and a urethane bond, has a viscosity ranging from 4000 to 6000 mPa·s, and is a light yellow transparent liquid in appearance.

4. The anaerobic UV adhesive according to claim 1, characterized in that: The acrylic acid monomer is one or more of isobornyl acrylate and tetrahydrofuran acrylate.

5. The anaerobic UV adhesive according to claim 1, characterized in that: The peroxide initiator is a peroxide mixture.

6. The anaerobic UV adhesive according to claim 1, characterized in that: The photoinitiator is 1-hydroxycyclohexyl phenyl ketone.

7. The anaerobic UV adhesive according to claim 1, characterized in that: The filler is hydrophobic fumed silica.

8. The anaerobic UV adhesive according to claim 1, characterized in that: The filler type is one or more of TS720, R974 and R972.

9. The anaerobic UV adhesive according to claim 1, characterized in that: The color paste category is HostatintUV BLACKN30.

10. A method for preparing the anaerobic UV adhesive according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Prepare raw materials: weigh the following raw materials by weight: 40-60 parts of acrylic oligomer, 40-60 parts of acrylic monomer, 1-3 parts of peroxide initiator, 1-3 parts of photoinitiator, 3-5 parts of filler, and 0.03-0.06 parts of color paste; S2, mixing and stirring: adding the weighed raw materials into a stirring cup, placing the stirring cup in a blender, stirring at a rate of 1000 revolutions per minute for 100-200 seconds without turning on the vacuum pump, and stirring at a rate of 1000 revolutions per minute for 100-200 seconds with the vacuum pump turned on, to obtain a uniformly mixed glue solution; S3. Curing and application: Apply the glue to the pre-configured substrate surface and cure it under UV light for 11 seconds. Wait until the colloid returns to room temperature to obtain a colloid with good adhesion and is difficult to peel off.

Citation Information

Cited By

  • A leak prevention method

    TWI919770B